Avstrijska čitalnica Univerzitetne knjižnice Maribor v funkciji medkulturnega dialoga - Škofljanec, Mateja (Organizacija znanja, 2007)
There are 52 Austrian Libraries in 24 European countries. They offer access tolibrary materials and information, promote the German language and organise different events: film evenings, international confereces, literary evenings. The Austrian Library of the University of Maribor Library is the third oldest Austrian Library and was opened in 1990. We have organised many international conferences, writers came to visit and the film evenings are permanently in our programme. We work very closely with institutions in and outside Slovenia.In the function of intercultural dialogue our Austrian Library of theUniversity of Maribor Library is a link between two different countries, cultures and languages.
Keywords: avstrijske čitalnice; Evropsko leto medkulturnega dialoga; medkulturni dialog; Univerzitetna knjižnica Maribor